MOLECULAR DOCKING STUDY OF LEAD COMPOUNDS FROM ELATHY CHOORANAM A SIDDHA FORMULATION AGAINST HELICOBACTER PYLORI UREASE (Journal of Pharmaceutical Negative Results, 2023)
Helicobacter pylori (H. pylori), infection has strong association with development of gastritis, peptic ulcers, and stomach cancer. Though there exist unclear and complex treatment modalities for H.Pylori infection, recent step-up in herbal medicines can be a way out for these intricate research arena. Several efforts have been taken off late to transform traditional medicine into a modern industry in order to deliver healthcare to the common people. The present study was aimed at identifying potential lead phytochemicals from traditional anti-ulcer Siddha medicine ElathyChooranam that can inhibit H. pylori and possibly serve as adjuvant treatments. Here, in silico molecular docking was performed using auto dock tools to identify potential inhibitors that favour the binding with the core amino acids (LYS-445 and VAL-473, TYR-475) which inturn would hinder the function of the enzyme H pylori Urease.Based on the results of the computational analysis it was concluded that the bio-active compound’s like β-sitosterol , Kaempferol , Piperine, Abiesin, Gingerenone-A and Nerolidol present in the Siddha formulation ElathyChooranampossess significant binding against the target H pylori urease Thereby it can be concluded that these compounds may exert promising anti-ulcer activity by inhibiting the enzyme H pylori urease which is regarded as the predominant virulence determinant of H pylori that catalyze the hydrolysis of urea to ammonia in the pathogenesis of ulcer.